Growth Curve and Nutrient Accumulation in Lettuce for Seed Production Under Organic System - Jolinda Mércia de Sá; Antonio Ismael Inácio Cardoso; Daniel Seiji Seguchi; Jorgiani de Ávila; Joseantonio Ribeiro de Carvalho; Emanuele Possas de Souza; Pâmela Gomes Nakada-Freitas (Horticulturae, 2025)
Producing seeds in the organic production system still requires a lot of information regarding the fertilization and nutritional requirements. Thus, the objective of this study was to determine the dry mass and macronutrient accumulation curve in lettuce for seed production, aiming at cultivation in an organic system. The treatments consisted of two phosphorus doses (320 and 800 kg ha−1 of P2O5, Yoorin® thermophosphate source). The crisp lettuce plants, cultivar Solaris, were collected at eight stages (0, 14, 28, 42, 56, 70, 84, and 98 days after transplanting—DAT) for an analysis of the proposed characteristics. A nonlinear sigmoid regression curve was fitted and the results demonstrated continuous plant growth, accompanied by a gradual increase in dry matter throughout the experimental period, regardless of the phosphorus dose studied. The vegetative part of the lettuce plant shows slow initial growth, followed by acceleration up to the beginning of flowering (70 DAT), and stabilization after this period. The reproductive part of the lettuce plant begins to grow from 56 DAT, increasing the daily nutrient demand until the end of the seed maturation and harvest at 98 DAT. The dose of 800 kg ha−1 of P2O5, the lettuce plant accumulated 1527.7, 308.2, 2922.6, 1658.4, 416.0, and 197.6 mg per plant of N, P, K, Ca, Mg, and S, respectively. The dose of 320 kg ha−1 of P2O5, the lettuce plant accumulated 1743.1, 256.9, 2575.7, 1210.2, 358.8, and 185.5 mg per plant of N, P, K, Ca, Mg, and S, respectively. The greatest demand for nutrients in the plant occurred between 55 and 88 DAT.